An IS711 Element Downstream of the bp26 Gene Is a Specific Marker of Brucella spp. Isolated from Marine Mammals - Cloeckaert, Axel (American Society for Microbiology, 2000)
DNA polymorphism of the bp26 gene, coding for a diagnostic protein antigen for brucellosis, was assessed by PCR and restriction fragment length polymorphism analysis using primers to amplify the bp26 gene with its flanking regions. Surprisingly, whereas PCR performed on DNA of the reference strains of the six recognized Brucella species produced a product of the expected size (1,029 bp), PCR performed on DNA of three representative strains from marine mammals (from a seal, a dolphin, and a porpoise) produced a larger product, of about 1,900 bp. Nucleotide sequencing of the 1,900-bp PCR products revealed the presence of an insertion sequence, IS711, downstream of the bp26 gene and adjacent to a Bru-RS1 element previously described as being a hot spot for IS711 insertion. PCR performed on a large number of field strains from different geographic origins and from marine mammal isolates indicated that the occurrence of an IS711 element downstream of the bp26 gene was a feature specific to the marine mammal Brucella strains. Thus, this PCR assay is able to differentiate Brucella terrestrial isolates from marine mammal isolates and could be applied for diagnostic purposes.